Структура та компетенція мирових судів Волинської губернії у період правління Української Центральної Ради(березень1917 – квітень1918) - Яцишин, Михайло Михайлович; Yatsyshyn, Mykhailo M. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано структуру та компетенцію мирових судів Волинської губернії у період правління Української Центральної Ради(березень1917 – квітень1918). Розглянуто правовий статус мирових судів у досліджуваний період, а також їх роль в здійсненні судочинства. Діяльність мирового суду на Волині охоплювала широке коло правопорушень і регулювалась загальноімперськими законами та постановами Тимчасового уряду. Завдяки виваженості своїх присудів мирові судді користувалися авторитетом серед місцевих жителів, свідченням чого слугує надзвичайна завантаженість судів та всезростаючий обсяг справ. The article analyzes the structure and competence of magistrate courts of Volyn province during the the Ukrainian Central Council governing (March 1917 - April 1918). The emphasis is laid on the legal status of magistrate courts in the investigated period, and their role in the administration of justice and implementation of legal proceedings. The magistrate courts of the Volyn province in the times of the Ukrainian Central Council were the lowest subdivision in the judicial system and presented the judiciary bodies in the field of minor legal relationships, both criminal and civil. The activity of the magistrate court in Volyn covered a wide range of offenses and was regulated by general imperial laws and resolutions of the Provisional Government. Due to the prudence of their judgments, the magistrates enjoyed great authority among locals, the evidence of which is the extraordinary workload of the courts and the increased amount of cases. In view of the short historical period of existence, the UCC was unable to rebuild the judicial system, which in many respects functioned as in the previous period. In general, the magistrates in theVolyn province provided support for the rule of law and actually effective judicial proceedings.
Structure and Competence of MagistrateCourts in Volyn Province During the Ukrainian Central Council Governing (March 1917 - April 1918)
Keywords: мирові суди; з’їзди мирових суддів; судова система; Українська Центральна Рада; Волинська губернія; окружні суди та судові палати; magistrates; congresses of magistrates; the judiciary; the Ukrainian Central Council; Volyn province; district courts and court chambers